Uma historiografia do processo brasileiro de gramatização da colocação pronominal em gramáticas oitocentistas - Ferreira, Emily Gonçalves de Medeiros (2021)
The purpose of this dissertation is investigate the emergence and development of the grammatization process of pronominal placement in Brazilian Portuguese in grammars published at the course of the 19th century. The research is situated within the domain of Linguistic Historiography, here understood as a methodologically and epistemologically aware achievement to register the history of language studies (KOERNER, 1996; 2014a; 2014b; SWIGGERS, 2010; 2012; 2013; 2015; 2019). In addition to the concept of grammatization itself (AUROUX, 2014 [1992]), three categories of analysis guide the research: rhetoric, according to the conflict model (MURRAY, 1994); research agenda (SWIGGERS, 2013); and layers of linguistic knowledge (SWIGGERS, 2004; 2019). For the analysis, 16 Brazilian grammars published in the 19th century, by Moraes Silva (1806; 1824); Costa Duarte (1829; 1877); Beserra (1861); Villeroy (1870); Sotero dos Reis (1871); Rabello (1872); Fr. Caneca (1876); Ernesto Carneiro Ribeiro (1881); Julio Ribeiro (1881; 1885; 1899); Pacheco & Lameira (1887); João Ribeiro (1889); and Freire da Silva (1894). These grammars were, firstly, examined in their immanence and, later, aligned with each other from an cronological perspective of Brazilian grammatical studies that divides the 19th century into three periods: originating period (1801-1820), rationalist period (1821-1880) and “scientific” period (1881- 1900). As results, in the analysis of contextual layer, we observed the crossing of different perspectives on the language (derived from the Greco-Latin tradition, from the sensualist philosophy, from Port-Royal, from the historical-comparative current, from philological studies); on the other hand, despite the different assumptions assumed by the authors, the 19th century Brazilian grammars are crossed by a pedagogical-normative purpose that indirectly influenced the development of the pronominal placement approach. In the theoretical layer, in each period, we identified a relative stability in relation to the assumptions that underlie the constitution of the works. Besides, changes in general and specific concepts underlie the process of emergency and autonomy of the pronominal placement, despite the divergences assumed by the authors. As for the technical and documentary layers, we found that the constitution of rules gained strength, especially in the “scientific” period, even though the works of Costa Duarte (1829; 1877) and Carneiro Ribeiro (1881), from a rationalist direction, occasionally regulate the phenomenon; moreover, all the works that addressed this linguistic phenomenon presented short sentences elaborated by the authors themselves as examples. Finally, we observe that the consolidation of the pronominal placement grammatization process probably occurred in “scientific” period. This status, however, was gradually achieved: it emerged, first, as a secondary aspect to other concepts, then starting to be perceived as a language phenomenon, until it effectively became an independent object on the brazilian’s grammatical approach at the 19th century